2015
DOI: 10.1177/230949901502300313
|View full text |Cite
|
Sign up to set email alerts
|

Volar Locking Plate Osteosynthesis for Distal Radial Fractures

Abstract: Volar locking plate fixation followed by early rehabilitation for distal radial fractures achieved good outcome, with a low rate of implant-related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…After the removal of duplicates, and screening of the titles, abstracts, and full texts, 112 articles were included in the systematic review ( Fig. 1 ) ( 6 , 10 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , ...…”
Section: Resultsmentioning
confidence: 99%
“…After the removal of duplicates, and screening of the titles, abstracts, and full texts, 112 articles were included in the systematic review ( Fig. 1 ) ( 6 , 10 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the locking plate, at present, the "small" volar locking plate is often used, which has the advantages of good internal fixation and less complications [36]. Simic et al reported that the wrist and hand function recovered well using the dorsal small locking plate fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, locked plate fixation may introduce a bulged mass because of mismatched bone-implant contours. 33 Especially, the locked plate is placed in the dorsal Wu side to treat the collapsed and dorsal tilt radius with an opening wedge osteotomy. 32 In the current study, a high correlation between MMWS and DASH Score is found ( p ¼ À0.92 and À0.87, respectively) preoperatively and at the latest follow-up.…”
Section: Discussionmentioning
confidence: 99%